Design and Implementation an e-Hospital System at Kurdistan - Ahmed, Mohamed Jasim; Zeebaree, Subhi R. M. (Kurdistan Journal of Applied Research, 2017)
The utilization of Information and Communication Technologies (ICT) have developed quickly. Traditional Healthcare (TH) which designates paper-predicated system is expeditious giving way to e-health system in most developed countries. Virtually all hospitals in the Kurdistan Region (KR) are utilizing TH. This paper deals with designing and implementing a web based electronic hospital system (WBEHS) in Shorsh General Hospital (SGH) in Slemani city. The system solves traditional style quandaries by transmuting the traditional paper-based healthcare system into a fully electronic system containing multi modules such as (Physician, X-Ray, Pharmacy, Laboratories, Ultrasound). The staff of SGH participated in the implementation and obtaining the results which have been evaluated by utilizing System Usability Scale (SUS). The overall evaluation score of the questionnaire was (79. 459%) which can be considered as a good result.